Paracoccidioidomicose em um adolescente imunocompetente: uma doença negligenciada - Aléxia Alves Cabral; Cecília Pereira Silva; Maria Cristina Carvalho do Espírito Santo; Denise A. Castro; Tainá Barros Ventura; Rafael Pereira Silva; Naiany Campos Rego (Sociedade Brasileira de Pediatria, 2023)
Acute Paracoccidioidomycosis (PCM) represents 5 to 10% of total PCM cases. The estimated incidence varies between 1-4 cases for 100.000 inhabitants in the endemic regions of Brazil. It is known that PCM can coexist with other systemic mycoses such as Histoplasmosis. We report a case of a 10-year-old adolescent from Barra Mansa, RJ, Brazil. He was hospitalized after recurrent visits to the emergency department for approximately one month, presenting with non-bloody diarrhea, weight-loss of 6kg in six weeks, dry cough and nocturnal fever (average temperature 38ºC). Counterimmunoelectrophoresis and lymph node biopsy were positive for Paracoccidioides brasiliensis. The treatment consisted of Amphotericin B IV 0,6 mg/kg of body weight per day for 10 days and Itraconazole PO 200mg per day for 12 months. After 5 years, the patient remains asymptomatic. Reports of similar cases are scant in the literature and, the few encountered, are of immunocompromised children. The incidence and prevalence estimation of PCM might be inaccurate due to underdiagnosis and under-reporting.